A quantification of the treadmill 6-min walk test using the MyWellness Key™ accelerometer - S. Andy Sparks; Nathan P. Hilton (Elsevier, 2015)
Background: Accelerometers have been suggested to provide additional information during the 6-min walk test which may be useful in evaluating changes in functional exercise capacity. The aim of the study was to identify whether the additional information measured by the MyWellness Key™ (MWK) accelerometer during a treadmill 6-min walk test (t-6MWT) was related to currently used outcome measures. Methods: Fifteen participants (9 males, 6 females) performed a self-paced t-6MWT. Respiratory gas analysis and walking distance were measured whilst wearing the MWK. Results: A significant correlation was established between activity counts and 6-min walk distance (6MWD) (r = −0.847, p < 0.001) yet not 6-min walk work (6MWW) (r = −0.337, p = 0.220). Energy expenditure estimated by the MWK was strongly correlated to 6MWW (r = 0.938, p < 0.001) but not 6MWD (r = 0.477, p = 0.072). The MWK significantly underestimated energy expenditure (36.73, CI = 33.9-39.7 kcal) compared to gas analysis (54.35, CI = 46.2-61.4 kcal) demonstrating poor agreement between the two analyses (Bias = −17.61 kcal, Limits of agreement = −37.4, +2.2 kcal). Measurement of time spent undertaking light, moderate, and vigorous physical activity was not significantly different (p > 0.05) between the MWK and gas analysis. Conclusion: Estimated energy expenditure provided by the MWK was strongly correlated to 6MWW; however, MWK underestimated energy expenditure as measured by gas analysis. The MWK may provide outcome data that supplement those currently provided by the 6MWD for functional capacity assessment during the t-6MWT.